2014
DOI: 10.1515/rnam-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Energy equation for certain approximate models of long-wave hydrodynamics

Abstract: International audienceA new derivation of completely nonlinear weakly-dispersive shallow water equations is given without assumption of flow potentiality. Boussinesq type equations are derived for weakly nonlinear waves above a moving bottom. It is established that the total energy balance condition holds for all nonlinear dispersion models obtained here

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Here we continue the recent investigations in [3][4][5][6]. It is necessary to acknowledge [7][8][9][10] and others as the first studies on this theme.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Here we continue the recent investigations in [3][4][5][6]. It is necessary to acknowledge [7][8][9][10] and others as the first studies on this theme.…”
supporting
confidence: 59%
“…Therefore, a mod ification of the models of these chains is required. Cer tain steps in this direction are made in [14] in which, in particular, it was shown that the modified models of this group admit the writing of the momentum bal ance equation in a laconic quasi conservative form.…”
Section: Hierarchy Of Shallow Water Modelsmentioning
confidence: 99%
“…The procedure of finding the quantities E and q E follows a similar outline as the derivations in [26] for a class of Boussinesq systems and [27] for the KdV equation. Expressions for energy functionals associated to Boussinesq systems have also been developed in [28]. The analytical results are put to use in the study of undular bores.…”
Section: Introductionmentioning
confidence: 99%
“…Since the structure of the equations of the full nonlinear dispersive model holds true for the weakly dispersion model on a sphere, as well as the model of weakly dispersive flows over weakly deformable bottom [4], the algorithm for the numerical solution of the full nonlinear dispersive equations can be transferred unchanged also to this approximate models.…”
Section: Discussionmentioning
confidence: 99%
“…In [3,4] with using the unified approach to a construction of long-wave approximations, the hierarchy of hydrodynamic models, which possess the physically meaningful properties inherited, has been built. The hierarchical chains of shallow water models of first-and secondorder long-wave approximation enclosed in each other are constructed on a rotating sphere and on a plane.…”
Section: Introductionmentioning
confidence: 99%